11. Implementasi Penggunaan Scan Barcode Boarding Pass - Wawan Riyanta; Adiguna Aji Wijayanto (Jurnal Manajemen Dirgantara, 2019)
This study aims to determine the implementation of used machine scanned for boarding pass passanger when entering the waiting room and find out what obstacles occur in the field related to the implementation of used machine scanned for boarding pass barcodes passenger. This research was processed using qualitative methods. Which in qualitative research can retrieve data from the results of interviews and documentation. From the interviews and documentation in this study, it can be seen that the implementation of machine scanned barcodes boarding pass at Radin Inten II Lampung Airport is effective and useful to help smooth flights related to flight safety. This is a machine scanned barcode boarding pass used since 2017 and is very helpful for aviation security officers in checking the authenticity of passenger identity before entering the waiting room to reduce the occurrence of fraud that occurs such as falsification of flight documents that have occurred at Radin Inten II Lampung Airport.